2002
DOI: 10.1177/10442073020130020901
|View full text |Cite
|
Sign up to set email alerts
|

Leadership by People with Disabilities in Self-Determination Systems Change

Abstract: People with disabilities have been in the forefront of advancing self-determination services and policies. This article discusses the involvement of individuals in person-directed services and the roles of individual leaders with disabilities and disability organizations led by people with disabilities in shaping policies and systems. Findings from 3 surveys of the involvement of individuals with disabilities in disability organizations and agencies are presented. Cross-disability principles for self-determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Although the current leadership was playing a vital role in the non-profit sector, the findings of this study also indicate that there was concern about the low priority given to leader development, particularly with younger persons with disabilities entering the movement. The visionary approach to leadership that was so important 20 years ago must now give way to a new leadership direction that can carry on the vision and implement it within the new social movement (Powers et al, 2002). An elaboration on this subject can be found in a more extensive analysis (Hutchison et al, 2007).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the current leadership was playing a vital role in the non-profit sector, the findings of this study also indicate that there was concern about the low priority given to leader development, particularly with younger persons with disabilities entering the movement. The visionary approach to leadership that was so important 20 years ago must now give way to a new leadership direction that can carry on the vision and implement it within the new social movement (Powers et al, 2002). An elaboration on this subject can be found in a more extensive analysis (Hutchison et al, 2007).…”
Section: Resultsmentioning
confidence: 98%
“…A growing literature is now suggesting that user-led disability organizations are calling to be recognized as the voice of people with disabilities and in that role are contributing to a broad social movement concerned with human rights, citizenship and policy change (Powers et al, 2002;Stienstra & Wight-Felske, 2003). The role of user-led organizations in Canadian policy formation was studied by Boyce and colleagues, who found increased participation by people with disabilities in policymaking (Boyce et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the results of a study on leadership emergence among people with learning disabilities showed that having a disability negatively impacted both peer perceptions of leadership potential and leadership role occupancy, although no significant differences in leadership effectiveness were indicated in supervisor and peer evaluations (Luria, Kalish, & Weinstein, 2014). Our understanding of leadership by neurodiverse individuals is further limited by an assumption that their influence will be predominantly on similar others (Powers et al, 2002). As such, leadership among people with disabilities has largely been conceptualized as advocacy, role modeling, or other consultative behaviors (Carter, Swedeen, Walter, Moss, & Shin, 2011; Powers et al, 2002).…”
Section: Can Neurodiverse Individuals Be Leaders?mentioning
confidence: 99%
“…Despite slow progress in fostering ongoing research-community partnerships and increasing the number of researchers from marginalized communities, the majority of researchers still come from racial, cultural, social, educational, and economic worlds that are vastly different than those from the communities with which they desire to partner. This separation of academic researcher and communities of people with DD is further compounded by power differential tied to historic medical model perspectives emphasizing incapacity of people with DD, professionals' assumed expertise and charge to objectively assess and make decisions in their best interests, and historically limited investment in supporting the leadership development of people with DD (Dybwad & Bersani, 1996;Powers et al, 2002). Individuals with DD are generally viewed as the targets and benefactors of research, not as experts or leaders.…”
Section: Lack Of Ongoing Connections Between Academic Researchers Andmentioning
confidence: 99%